Reasonable accommodation for students with disabilities/learning disabilities: perspectives of university faculty, staff and students - BAKRI, SEREEN TALAL (Trinity College Dublin. School of Education. Discipline of Education, 2019)
In recent years, in Saudi Arabia, students with disabilities (SWDs) including students with a learning disability (SLD) have been enroling in post-secondary education in growing numbers. The growth of this population within the overall student body presents new challenges at institutions of post-secondary education given that collaboration between faculty members and disability services staff is necessary if the needs of these students are to be accommodated. It is mandated by law that post-secondary educational institutions must provide dedicated support services for SWD/SLDs. This requirement is set out in the Disability Code and the Regulation of Students with Disabilities’ Rights in Higher Education Institutions in the Gulf Cooperation Council (GCC), which stipulates that these students must have access to educational programs equal to that afforded to their peers. Further, SWD/SLDs should be provided with other forms of services to minimize disadvantages arising from a disability. The purpose of this research is to analyze feedback on this topic collected from three target groups: female faculty members, female SWD/SLDs, and female Centre for Disability Support Services (CDSS) staff. A survey with open-ended and closed-ended questions and semi-structured interviews were used to collect their feedback. Female faculty members of various academic seniority levels ranging from lecturer to full professor (non-nationality-specific) at King Saud University (KSU) and Princess Nourah University (PNU) were the first group targeted. The faculty members belong to the Education and Art Schools, where most SWD/SLDs are enroled. Surveys were distributed to all 305 female faculty members at KSU and all 352 at PNU, of whom 58.9% responded (387 surveys were completed) (n = 176 from KSU and n= 211 from PNU). To obtain greater insight, fourteen faculty members were interviewed regarding their experience in relation to providing reasonable accommodations to SWD/SLDs. Female SWD/SLDs from these same two universities comprised the second target group. To be included in this research, the students had to be registered with their Centre for Disability Support Services (CDSS), and they had to be eligible for reasonable accommodations in the academic context. Six students from each university were interviewed in order to gain insight into their experiences in post-secondary education and the challenges they face in that context. Two members of CDSS management were the third group targeted. These staff members are charged with providing information regarding the support services the CDSS provides to SWD/SLDs and creating training programs for other faculty and staff, often with a focus on the faculty. The findings of this study reinforce Bronfenbrenner’s ecological systems theory. It was observed that faculty members who directly interact with SWD/SLDs report being very willing to provide reasonable accommodations. However, the majority felt that they did not have adequate formal training to confidently meet the needs of the SWD/SLDs in their classrooms. A deficiency was also found in faculty members’ awareness and knowledge of disability legislation addressing the rights of SWD/SLDs, which is often a barrier to the provision of reasonable accommodations. Another issue identified in this study is the existence of a communication gap between faculty members and CDSS staff. For example, the faculty who participated in the interviews conducted for this study reported that the CDSS could do much more in regard to providing training courses and ensuring that the faculty are aware of relevant legislation. However, the majority of SWD/SLDs who were interviewed commended the services they had received directly from the CDSS. Yet, these students also stated that faculty members often lack understanding of both their disabilities and their specific educational needs’which are related issued that should be addressed. The students also raised another concern: They stated that some courses are deemed unsuitable for SWD/SLDs such that they still cannot enrol in all the courses open to their peers. This study presents the conclusion that, despite significant funding, most of Saudi Arabia’s institutions of higher education still lack adequate services for SWD/SLDs, which means that this student population is not adequately supported academically. There is vast room for improvement, especially regarding female students. Hence, it is proposed that disability legislation should become a requirement for all institutions of higher education in order to safeguard these students’ rights and secure equality for students of both genders.
APPROVED
Keywords: Higher education, disabilities, learning disabilities, accessibilty centres, centres for disabilitis support services